1987
DOI: 10.1007/bf00846422
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laughter and relaxation on discomfort thresholds

Abstract: Two experiments were conducted to test the proposal that laughter is a pain antagonist. In Experiment I, thresholds for pressure-induced discomfort of 20 male and 20 female subjects were measured after each subject listened to a 20-min-long laughter-inducing, relaxation-inducing, or dull-narrative audio tape or no tape. Discomfort thresholds were higher for subjects in the laughter- and the relaxation-inducing conditions. In Experiment II, 40 female subjects were matched for pressure-induced discomfort thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
1
4

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(75 citation statements)
references
References 10 publications
0
70
1
4
Order By: Relevance
“…People who are low in well-being have a more difficult time coping with pain than people who are high in well-being, and retrospectively overestimate their levels of pain (Keefe, Lumley, Anderson, Lunch, & Carson, 2001). Zelman, Howland, Nichols, and Cleeland (1991) found that people put into a positive mood showed greater pain tolerance than control subjects, and this finding was replicated by Cogan, Cogan, Waltz, and McCue (1987).…”
Section: Well-being Affects Physical Health and Painmentioning
confidence: 86%
“…People who are low in well-being have a more difficult time coping with pain than people who are high in well-being, and retrospectively overestimate their levels of pain (Keefe, Lumley, Anderson, Lunch, & Carson, 2001). Zelman, Howland, Nichols, and Cleeland (1991) found that people put into a positive mood showed greater pain tolerance than control subjects, and this finding was replicated by Cogan, Cogan, Waltz, and McCue (1987).…”
Section: Well-being Affects Physical Health and Painmentioning
confidence: 86%
“…An obvious hypothesis is that all these activities exploit the same psychopharmacological mechanism (the release of endorphins) as social grooming does in primates [25,26], and so provide a bridging mechanism (i.e. a form of grooming at a distance) that enables humans to bond social communities that are much larger than those that primates can bond by social grooming alone [12][13][14][15][16][17][18][19][20][21][22][23][24][25]56]. This possibility awaits detailed testing.…”
Section: Discussionmentioning
confidence: 99%
“…A tentative answer derives from the fact that humour can have analgesic properties: patients allowed to watch comedy videos required less pain medication than those who watched control videos [13][14][15]. However, whether patients laughed was never explicitly tested in these experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Positive valenced emotions including experimentally-induced positive mood (Akins et al, 1983;Bruehl et al, 1993;Cogan et al, 1987;Weisenberg et al, 1998;Zelman et al, 1991;Zillmann et al, 1996), sexual excitation (Komisaruk and Whipple, 1986;Meagher et al, 2001;Rhudy et al, 2008), and relaxation (Cogan et al, 1987;Westcott and Horan, 1977) consistently lead to reduced pain/nociception. However, the degree of inhibition is determined by the intensity of the emotional state (as assessed by arousal level), with more intense positive emotions (i.e., sexual excitement) eliciting the greatest inhibition (Komisaruk and Whipple, 1986;Rhudy et al, 2008).…”
Section: Relations To Previous Studies Of Emotion and Pain/nociceptionmentioning
confidence: 98%